2019
DOI: 10.3390/vaccines7040136
|View full text |Cite
|
Sign up to set email alerts
|

Utilising Group-Size and Home-Range Characteristics of Free-Roaming Dogs (FRD) to Guide Mass Vaccination Campaigns against Rabies in India

Abstract: Adequate vaccination coverage of free roaming dogs (FRD) against canine rabies is not achieved primarily due to difficulties in administering parenteral vaccinations to this population. One factor associated with this difficulty is the tendency of FRD to form groups, which increases their aggressive behavior, resulting in a significant risk of dog-bites for the vaccinators. This study investigated factors that influenced FRD forming groups and their home-ranges, using data obtained from photographic capture-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, no study investigated FRDD roaming behavior in Africa so far. Often, data were collected using Global Positioning System (GPS) tracking devices ( 1 4 , 6 8 , 11 16 , 18 20 ), but other tools, such as capture–recapture ( 10 , 21 ) or interviews ( 9 ), were also used to collect data on FRDD roaming behavior. Home range ( 2 , 14 , 17 , 19 ), the area a dog commonly uses for normal activities, such as breeding or foraging, and distance from home ( 12 , 13 , 20 ) were applied to describe and investigate dog roaming behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no study investigated FRDD roaming behavior in Africa so far. Often, data were collected using Global Positioning System (GPS) tracking devices ( 1 4 , 6 8 , 11 16 , 18 20 ), but other tools, such as capture–recapture ( 10 , 21 ) or interviews ( 9 ), were also used to collect data on FRDD roaming behavior. Home range ( 2 , 14 , 17 , 19 ), the area a dog commonly uses for normal activities, such as breeding or foraging, and distance from home ( 12 , 13 , 20 ) were applied to describe and investigate dog roaming behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies in Brazil showed that higher stray dog density was associated with the proximity with potential sources of food, such as the university restaurants or commercial food outlets ( 10 , 27 ). Another study in India concluded that groups of FRDD were more likely to be seen close to garbage sites ( 21 ). This suggests a substantial impact of feeding practices and quality and quantity of feed provided on FRDD movements.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies assessing the community's awareness of canine mediated rabies in endemic countries through knowledge, attitudes and practices (KAP) studies have resulted in an overall improvement in the community's knowledge of the disease; however, gaps in the knowledge and misinformation regarding the disease remain, especially in the rural and socio-economically poor sectors of the community (Tiwari et al 2019b). Not surprisingly, crucial information about the disease eludes the most vulnerable populations, such as school-age children, families with children less than 14 years of age and religious groups that support FRD in the human settlements (Madjadinan et al 2020;Tiwari et al 2019a).…”
Section: (A) Knowledge Attitudes and Practicesmentioning
confidence: 99%
“…In a previous publication, we advocated investment in studies on FRD behaviour and demography to forecast the required combination of oral and parenteral vaccines in canines for rural and urban localities (Tiwari 2019;Tiwari et al 2019b). In a country, such as India, where the average longevity of an individual FRD is estimated to be only 2.8 years (Totton et al 2010), maintaining immunity level against rabies in dog population to break virus transmission will require several canine massvaccination campaigns over multiple years.…”
Section: (B) Human Canine Anti-rabies Vaccination and Dog Population Managementmentioning
confidence: 99%
“…Further, we focused on working on the felt need for canine vaccination, which is imperative for its acceptance [43,44]. Mass vaccination of dog in India are driven by Non-Governmental Organisations and dependent on trust based funding [45][46][47]. Here we present the results where community members facilitated and actively contributed to conduct canine rabies vaccination and sterilization.…”
Section: Plos Onementioning
confidence: 99%